Glitching justice: Audio visual links and the sonic world of technologised courts - Carolyn McKay (Law Text Culture, 2020)
My earlier work on the prison endpoint of audio visual link technologies found that a ‘soundtrack of incarceration’ often infiltrates prison audio visual link studios and may be unintentionally transmitted to the remote courtroom (McKay 2016, 2017, 2018a,b). This article shifts attention to the courtroom endpoint of audio-visual links to examine the audio dimensions of this form of communication. Drawing on case law and transcripts from Australia, New Zealand and England, this article identifies a range of acoustic issues, or glitches, that are analysed through the lens of emergent criminological and socio-legal understandings of sound to grasp the sonic world of increasingly technologised courtrooms.